Kelayakan Komposit rPET-Aerosil Sebagai Filamen 3D: Studi Eksperimental Terhadap Sifat Mekanik - Zulky Khoiri; Sugianto Sugianto; Idiar Idiar (Jurnal Inovasi Teknologi Terapan, 2026)
This study evaluated the feasibility of aerosil-reinforced recycled PET (rPET) plastic composite as a filament raw material for 3D printing. Experiments were conducted by varying the aerosil concentration to analyze its effect on mechanical properties based on tensile tests (ASTM D638) and impact tests (ASTM D256). The results showed that the addition of 3 g of aerosil resulted in the highest tensile strength of 10.3 MPa, while the optimal elastic modulus was achieved at the addition of 1.5 g (1993 MPa). Although the overall tensile and elongation properties were still below the standard for commercial PETG filaments, the material's impact toughness actually increased. The addition of 2.25 g of aerosil resulted in the highest impact strength of 145 J/m², which exceeds the standard PETG. It was concluded that the rPET-aerosil composite is worthy of consideration as an environmentally friendly alternative filament, especially for applications that prioritize impact resistance, with the optimum aerosil composition ranging from 2.25-3 grams.